2020
DOI: 10.1055/s-0040-1713107
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Hematoma as Unexpected Complication of COVID-19 Infection

Abstract: Novel coronavirus disease-2019 (COVID-19) is an ominous infectious disease that seems capable to attack any organ system, leading in the most severe cases to patient death. COVID-19 has been associated with multiple cardiovascular complications of inflammatory and immune origin, leading to a wide spectrum of vascular damage, myocardial injury, stroke, and pulmonary obstruction. We report the case of a patient with COVID-19 infection who developed an acute aortic syndrome with the characteristics of aortic intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The characteristics and demographic features of the total of 45 COVID-19 patients with CI included in the selected case reports and case series are demonstrated in supplementary table 3 [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. Patients' age ranged from 38 days to 74 years and approximately 62% of them were males.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics and demographic features of the total of 45 COVID-19 patients with CI included in the selected case reports and case series are demonstrated in supplementary table 3 [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. Patients' age ranged from 38 days to 74 years and approximately 62% of them were males.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all studies (except Del Barba et al, 2020, Latimer et al, and Zeng et al, 2020) reported elevated CRP and eight studies reported CRP levels above 200 mg/L [ [20] , [21] , [22] , [26] , [27] , [28] ] . IL-6 was detected in multiple studies at elevated levels ranging from 17.06 to 7305 pg/mL [ 21 , 22 , 24 , 26 , 32 , 33 , [36] , [37] , [38] , 40 ]. Ferritin levels ranging from 600 to 7634 ng/mL were reported [ 21 , 22 , 26 , [28] , [29] , [30] , [32] , [33] , [34] , 36 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At our center, we treated an acute dissection of the aorta in a patient already known as positive to SARS‐CoV‐2 while isolating at home. The course was burdened by respiratory complications and the need for prolonged ventilation, but in the end, the patient survived and was discharged 29 …”
Section: Discussionmentioning
confidence: 99%